Islam dan Plurarisme Budaya (Toleransi Beragama di Era Abbasiyah) - Al Fahmi, Faiz Fikri; 'ulfadilah, annisa (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study aims to explore the concept of tolerance in Islam as practiced during the Abbasid Dynasty, especially in the interaction between Muslims and non-Muslims, and to analyze the views of the Imams of the Schools and contemporary scholars regarding the values ​​of tolerance in building an inclusive, harmonious, and respectful society. This study uses a qualitative approach with a library research method. Data were collected through literature reviews from various sources, including classical books, historical documents, and analysis of the views of the Imams of the Schools and contemporary scholars. This approach aims to gain an in-depth understanding of the practice of tolerance and its contribution to the development of Islamic civilization in the Abbasid era, especially through institutions such as Bayt al-Hikmah. This study found that the Abbasid Dynasty was an example of the successful implementation of religious tolerance through inclusive policies and collaborative approaches in various aspects of life. The Imams of the Schools emphasized the importance of tolerance as a basis for social interaction, both among Muslims and non-Muslims. Institutions such as Bayt al-Hikmah played an important role in encouraging cross-cultural and religious interaction, resulting in intellectual and social progress. These tolerance values ​​not only have an impact on political stability, but also make a significant contribution to building an advanced and diverse Islamic civilization. This study also emphasizes the importance of implementing tolerance values ​​in everyday life to create a harmonious society in the modern era.